Robust controller for active suspension with hydraulic dynamics - Md. Sam, Yahaya (IEEE, 2004)
The objective of this paper is to present a new control technique for controlling of an active suspension system with hydraulic dynamics for a quarter car model. The purpose of a car suspension system is to improve the riding quality while maintaining good handling characteristics subject to different road profiles. The objective of designing a controller for a car suspension system is to improve the riding quality without compromising on the handling characteristic by directly controlling the suspension forces to suit the road and driving conditions. In order to achieve the desired ride comfort and road handling and to solve the mismatched condition in the system modeling, a proportional-integral sliding mode control technique is presented to deal with the system and uncertainties. Extensive simulations are performed for different road profiles and the results showed that the proposed controller performed well in improving the ride comfort and road handling for the quarter car model using the hydraulically actuated suspension system.